The study of renewable heat incentive in Thailand - Teeramaethin Limwittayakorn (2018)
Renewable energy activities in Thailand are now continuously developed under the deployment of the national's Alternative Energy Development Plan (AEDP). However, renewable for heat activities require financial instrument or scheme to support the long-run widespread development. This study aims to investigate the appropriate renewable heat incentive (RHI) to encourage the renewable heat projects in Thai market by calculate from the fuel switching concept from various fossil fuels to renewable energy and applying the investment cost, fuel cost, operation and maintenance cost, depreciation along with engineering approaches with expected rate of return from 10 to15%. The replacement from five fossil fuels to 11 types of potential renewable energy, in gasification and direct heating technology, we found that anthracite replaced by RDF require the most support with 5.14 baht per kilogram of RDF. However, in the case of fuel switching to the expensive fuels such as oil and LPG to renewable energy such as biomass, the incentive values are all negative, which means that no support required. © (2014) Trans Tech Publications, Switzerland.